Human development index as an indicator of standard of living in southeast asian countries / Thirunaukarasu Subramaniam and Mohammad Raduan Mohd. Ariff - Subramaniam, Thirunaukarasu; Mohd. Ariff, Mohammad Raduan (2004)
Human Development Index or HDI which was coined by United Nations Development Programme (UNDP) in 1990 has become a standard measure of development in this world. The HDI is a composite index of four variables: life expectancy at birth; adult literacy rate; an aggregate primary, secondary and tertiary gross enrolment ratio; and a transformation of per capita GDP in US dollar purchasing power parity terms. This paper will explore the human development index in Southeast Asian (SEA) countries namely Malaysia, Indonesia, Thailand, Philippines, Singapore, Myanmar, Brunei, Cambodia, Laos PDR and Vietnam. The analysis shows that three out of the four SEA countries with the highest HDI has experienced a decline in its HDI. The recent economic crisis has brought an adverse impact on Singapore, Brunei and Thailand where there was a decline in the standard of living in these countries. Malaysia is the only country in SEA that has been having a steady growth in its HDI. The recent economic crisis has actually reduced the standard of living in most of the SEA countries.